Sprawy honorowe z udziałem polskich deputowanych do Dumy Państwowej Imperium Rosyjskiego w 1906 i 1913 roku (na materiale prasy rosyjskiej): Affairs of honour with participation of polish deputies of Imperial Duma in 1906 and 1913 (following Russian press) - Ivanov, Andrei (Przegląd Wschodnioeuropejski, 2021)
The article is concerned with the dueling incidents with participation of Polish deputies of Imperial Duma which took place in 1906 and 1913. The author reconstructs the causes, further things happening and results of these clashes as well as evidences their coverage from Russian news media and perception by Russian public. Special attention is put to the conflict of deputies belonging to the Polish group in Imperial Duma with the future Prime Minister of the Provisional Government A.F. Kerensky. The author proves that although on a moral level the injured party was Polish deputies, their chosen modus operandi was unsuccessful, and in the minds of the liberal democratic part of the Russian society Kerensky came out victor.